Controlled Donation After Circulatory Determination of Death: A Scoping Review of Ethical Issues, Key Concepts, and Arguments. Issue 3 (2021) - Murphy, Nicholas; Weijer, Charles; Smith, Maxwell; Chandler, Jennifer; Chamberlain, Erika; Gofton, Teneille; Slessarev, Marat
Abstract: Controlled donation after circulatory determination of death (cDCDD) is an important strategy for increasing the pool of eligible organ donors.